2003
DOI: 10.1007/s00464-002-9233-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon dioxide pneumoperitoneum on tissue blood flow in the peritoneum, rectus abdominis, and diaphragm muscles

Abstract: Despite high intraabdominal pressure, tissues surrounding the abdominal cavity, particularly the peritoneum, respond to insufflation of CO2 with increased blood flow, which may favor the growth of tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…The current study is in agreement with recent studies by us and others showing that CO 2 pneumoperitoneum is associated with a marked increase of blood flow in the peritoneum [5,21]. In addition, the current study provides evidence that this response is related to a local effect of CO 2 on the peritoneal tissue, and not to systemic alterations caused by prolonged CO 2 pneumoperitoneum.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The current study is in agreement with recent studies by us and others showing that CO 2 pneumoperitoneum is associated with a marked increase of blood flow in the peritoneum [5,21]. In addition, the current study provides evidence that this response is related to a local effect of CO 2 on the peritoneal tissue, and not to systemic alterations caused by prolonged CO 2 pneumoperitoneum.…”
Section: Discussionsupporting
confidence: 95%
“…In experimental animal studies, we and others have shown recently that insufflation of carbon dioxide (CO 2 ) into the abdominal cavity is associated with a marked blood flow increase in the peritoneum, even in the presence of high intraabdominal pressures comparable with those used during laparoscopic surgery [5,21]. This effect was not detected in control experiments with helium (He) insufflation [21].…”
mentioning
confidence: 94%
“…Notably, c-Met and uPAR are both increased in the setting of lowoxygen tension [28][29][30]. Animal experiments have demonstrated that a CO 2 pneumoperitoneum increases noninjured peritoneal blood flow [31,32]. In addition, our previous study demonstrated that the peritoneal tissue oxygen tension levels in noninjured peritoneum during a CO 2 pneumoperitoneum at a low IPP are elevated approximately two times the levels during laparotomy in a mouse laparoscopic model [8].…”
Section: Discussionmentioning
confidence: 96%
“…Whether CO 2 pneumoperitoneum will promote trocar implantation and extensive abdominal metas- tasis after laparoscopic tumor operation was widely discussed in recent ten years, but there were still no conclusions (Zhang and Kong, 2004;Leister et al, 2003;Yavuz et al, 2003 (Hirabayashi et al, 2002;Lecuru et al, 2002). But these factors could not explain why He pneumoperitoneum would not promote trocar implantation (Neuhaus et al, 1998).…”
Section: Discussionmentioning
confidence: 99%